Peran Krusial Perilaku Impulsif Dalam Memediasi Pengaruh Kualitas Informasi Dan Interaksi Terhadap Minat Wirausaha - Aditya, Dana; Agustini, Ni Ketut Yulia (Green Publisher Indonesia, 2025)
This study aims to analyze the mediating role of impulsive behavior in the relationship between information quality and interaction on entrepreneurial intention. Using a quantitative approach, data were collected through a survey targeting individuals who actively access entrepreneurial content via digital platforms. Structural Equation Modeling (SEM) was employed to examine both direct and indirect relationships among variables. The findings reveal that information quality and interaction intensity significantly influence impulsive behavior, which in turn affects entrepreneurial intention. Impulsive behavior serves as a critical mediator that enhances the impact of information quality and interaction on entrepreneurial motivation. These results suggest that entrepreneurial communication strategies should consider the emotional and spontaneous tendencies of the audience to effectively transform interest into concrete entrepreneurial actions.